ANLN and KDR Are Jointly Prognostic of Breast Cancer Survival and Can Be Modulated for Triple Negative Breast Cancer Control - Dai, Xiaofeng; Mei, Yi; Chen, Xiao; Cai, Dongyan (Frontiers in Genetics, 2019)
Purpose: KDR is the primary vascular endothelial growth factor receptor mediating survival, growth and migration of endothelial cells and is expressed also in various tumor cells through autocrine production. The PI3K/Pten pathway is one of the downstream signallings affected by KDR activation and most commonly altered in breast cancer. Here we investigate whether KDR expression is associated with members in PI3K/Pten signalling on the prognosis of breast cancer patients. Methods: PI3K/Pten pathway components were defined by mapping TCGA protein data to the KEGG database complemented by literature searching, accounting for 36 proteins subject to the interaction analysis with KDR on breast cancer patient survival. The identified interaction gene pair was subjected to in vitro validation following functional analysis. Results: ANLN was found to interact with KDR at translational and transcriptional levels using the public TCGA protein expression data and five gene expression data sets. Favorable prognosis corresponds to high protein but low gene expression of ANLN when KDR is highly expressed. Externally modulating cells toward low ANLN and high KDR gene expression was shown to transit triple negative cells toward a luminal-like state with increased level of ER and elevated sensitivity to Tamoxifen. Conclusion: Our study proposes a 2-gene panel prognostic of breast cancer survival and a novel therapeutic strategy for triple negative breast cancer control via transiting cancer cells towards a luminal-like state sensitive to established targeted therapy.